(untitled) (Baghdad Science Journal, 2008)
The synthesis of new benzodiazepine, imidazole, isatin, maleimide, pyrimidine and 1,2,4-triazole derived from 2-amino-4-hydroxy-1,3,5-triazine, via its cyclocondensation reaction with different organic reagents, is described. FT-IR, 1H-NMR and as well as 13C-NMR spectra disclosed the structures of the precursors and heterocyclic derivatives formed.